In-Between Identities: Signs of Islam in Contemporary American Writing. - John Waldmeir (Studies in Religion and the Arts, 2018)
For the writers and artists in In-Between Identities: Signs of Islam in Contemporary American Writing , contemporary Muslim American identity is neither singular nor fixed. Rather than dismiss the tradition in favor of more secular approaches, however, all of the figures here discover in Muhammad's revelation resources for affirming such uncertainty. For them, the Qur'anic notion of a divine "sign" validates creation, even that creativity born of contrasting if not competing assumptions about identity. To develop this claim, individual chapters in the book discuss Muslim faith in the work of poets Naomi Shihab Nye, Kazim Ali, Tyson Amir and Amir Sulaiman; novelists Mohja Kahf, Rabih Alameddine, and Willow Wilson; illustrator Sandow Birk; playwright Ayad Akhtar; and the online record of the 30 Mosques in 30 Days project.